A Scoping Review on Epidemiological Risk Factors and Treatment Modalities for Snakebites in India - Soumyajit Saha; Swati Behera; Srajana U. Kotekar; Shafeeq Hameed; Navya Vyas (Indian Journal of Public Health, 2025)
Background: Snakebite is a major public health concern in India and is associated with high rates of morbidity and mortality. Death and significant health repercussions caused by snakebites can be effectively mitigated with easy access to safe and effective antivenoms and enhanced awareness among healthcare professionals and the general public. Objectives: This review investigates the factors influencing snakebite outcomes and the current treatment options in India. Materials and Methods: The literature search was conducted using PubMed, Scopus, Google Scholar, Web of Science, and grey literature from World Health Organization and Government of India databases, focusing on studies published between 2012 and 2022. Inclusion criteria encompassed cross-sectional, intervention, descriptive, qualitative studies, case reports, and case series published in English, concentrating on snakebite envenoming. Results: Key findings included a lack of community awareness regarding early identification and management of snakebites, insufficient information on updated treatment protocols among healthcare providers, poor health-seeking behavior of victims, high reliance on untrained folk healers for initial treatment, and inadequate availability of anti-snake venom. These factors significantly impact snakebite-related outcomes. Conclusion: This scoping review provides valuable insights on the formulation of evidence-based policies that focus on reducing the impact of snakebite and improving patient outcomes in India, with the ultimate goal of achieving a 50% reduction in the number of deaths and cases of disability due to snakebite by 2030.